Nexos e reflexos da adaptação do enfermeiro à cultura organizacional - cristiano pinto dos santos; Giovana Calcagno Gomes; Wilson Danilo Lunardi Filho; Ariane da Cruz Guedes; Adriane Maria Neto de Oliveira; Ivanete Santiago da Silva Strefling (Universidade Federal de Santa Maria, 2019)
Aim: to understand the nexus and reflexes of nurses' adaptation to the organizational culture of nursing care in the hospital setting. Method: qualitative, exploratory-descriptive research, whose data were collected through semi-structured interviews with 12 nurses. For data analysis, the content analysis method was chosen, since it involves and apprehends subjective aspects, emerging two categories: the normalization of care and overcoming the normalizing adaptation. Results: the nurse, by providing the care, allows the organization's culture to make an agency on itself, being this adaptation optimized by the lack of exercise of the autonomy by the nurses and by a singular identity little consolidated. Final considerations: the reflex of the adaptation to the organizational culture makes the available care fragile, insufficiently promoting the nurse's proactivity. A longer working time favors the production of singular subjectivity.